Evaluasi Pengelolaan Persandian dalam Menjaga Keamanan Informasi Diskominfo dan Persandian Lombok Timur - Bardatul Gaffur; Muhammad Fachry Fachrudin (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2023)
The backgroud of this study is the leaking of data within the scope of the government, that is local government information security systems that have experienced leaks are secured, one of them is through encryption. Encryption is an activity in the field of data/information security which is carried out by applying the concepts, theories, arts and sciences of crypto and other supporting sciences in a systematic, methodological and consistent manner and is related to the ethics of the coding profession. Encoding is included in one of the mandatory affairs that are not related to basic services. This study aims to obtain information and describe how to evaluate encryption management in maintaining information security and to measure the level of readiness of Diskominfo dan Persandian Office in implementing information security using the Indeks KAMI 4.1 at Diskominfo dan Persandian East Lombok Regency. Qualitative research with descriptive inductive approach and interview, observation, and documentation techniques were used in data collection. Data reduction, data presentation, and data verification are used in data analysis techniques. Using the Context, Input, Process, Product (CIPP) evaluation theory, we get a situation that is still lacking due to the budget and operational coding, communication infrastructure and encryption infrastructure are still limited, the competence of coding human resources, awareness of information security is still low. Overcoming these obstacles, efforts were made to increase human resources and fulfill infrastructure in the field of encryption, increase government and public awareness about information security, build Command Centers and release LotimOne and LotimGo applications. Encryption management in maintaining information security is going well. Moreover, The final result to measure the level of readiness of information security using Indeks KAMI 4.1, which is 243 with the readiness status Not Eligible. And one of the products is the 2021 Public Information Disclosure Award (KIP) at the NTB provincial level.